Students' Learning Motivation Analysis of Class X on Distance Learning at SMA Negeri 1 Gubug: Analisis Motivasi Belajar Siswa Kelas X Pada Pembelajaran Jarak Jauh Di SMA Negeri 1 Gubug - Setyawan, Dani; Retnaningdyastuti, Retnaningdyastuti; Dian, Primaningrum (Journal of Vocational Education and Information Technology (JVEIT), 2023)
The research is motivated by the existence of the Covid-19 pandemic which raises various problems, especially for the application of distance learning program that requires students to carry out learning at home. The problem that discussed in this study is the level of learning motivation of 11th grade students at SMA Negeri 1 Gubug in distance learning program. The purpose of this research is to discover the factors that motivate students to participate in the learning program. This research used qualitative with a case study method. Respondents in this study were 3 students of 11th grade at SMA Negeri 1 Gubug, 3 parents of the respondents, 1 guidance and counselling teacher, and 3 homeroom teachers of the respondents. The data in this study were obtained through interviews, observation and documentation. Based on the analysis results of the research shows that the learning motivation of each student is different from another. Overall, the highest learning motivation is having a strong will to study, then having clear goals to achieve and also the desire to succeed, having conducive environment and the last is having the ability to solve problems. Subjects who have high learning motivation will be more capable to follow the learning process well, while those who have low learning motivation will find it difficult to follow the distance learning process. Suggestions from the researcher are for the family and teachers to pay more attention to the children/students and maintain good communication so that they can stay motivated in learning process.